Oxidized LDL, statin use, morbidity, and mortality in patients receiving maintenance hemodialysis - Wagner, Sandra; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; März, Winfried (Free radical research, 2017)
Statin treatment reduces the risk of cardiovascular mortality in the general population, but it has little or no benefit in hemodialyzed (HD) patients. This may reflect different underlying pathophysiology of cardiovascular disease (CVD) in patients treated with HD, maybe involving the oxidative stress. Our aim was to assess the association of oxidized low-density lipoprotein (oxLDL), determined by Mercodia oxLDL enzyme-linked immunosorbent assay (ELISA) kit, with major adverse cardiac events (MACE) and all-cause mortality in HD patients based on the AURORA trial (rosuvastatin vs placebo), and patients not on HD from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. We also assessed whether its decrease due to statin use improves these outcomes using Cox proportional hazard models. Baseline oxLDL level was 34.2 ± 13.8 U/L in AURORA and did not differ between treatment groups, and 74.6 ± 28.1 U/L in LURIC. Lower baseline oxLDL levels were associated with higher hazard ratios (HRs) for outcomes, but not anymore after adjusting for apolipoprotein B level in AURORA and was not related to mortality in LURIC. OxLDL levels decreased by 30.9% between baseline and 3 months in the statin-treated group and increased by 10.5% between 3 and 12 months. Nevertheless, oxLDL reduction was not significantly associated with adjusted HRs for MACE and for all-cause mortality. These results showed no association between oxLDL and MACE after adjustment on apolipoprotein B, which may relate to the properties of the method used for oxLDL. Our results also showed no benefit for oxLDL reduction by rosuvastatin on outcomes. Future clinical trials are needed to define the relative CVD risks and benefits of other modalities of oxidative stress modification in this population.